2020
DOI: 10.9734/ejmp/2020/v31i1130298
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Callus in Leaf Explants of Crinum americanum L. (Amaryllidaceae)

Abstract: Amaryllidaceae include plant species that present alkaloids with analgesic, anti-cancer, anti-bacterial, anti-viral, anti-fungal and anti-malarial activities. Due to this pharmacological value, several species of this family have been widely studied and among them is White lilly, Crinum americanum. The objective of this work was to induce callogenesis on leaf explants of C. americanum cultivated in vitro for future production of alkaloids. Leaf explants were grown on a culture medium (solid) Murashige and Skoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Callogenesis could be a beneficial experimental system for monitoring alkaloid biosynthesis (Tarakemeh et al, 2019). The effect of PGRs on callogenesis was also studied by Gomes-Copeland et al (2020) and they reported that the type and concentration of PGRs affected the percentage of in vitro callogenesis from the explants of Crinum americanum L. (Amaryllidaceae). Corresponding to these findings, the concentrations used in our study had an influential role in callus formation, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Callogenesis could be a beneficial experimental system for monitoring alkaloid biosynthesis (Tarakemeh et al, 2019). The effect of PGRs on callogenesis was also studied by Gomes-Copeland et al (2020) and they reported that the type and concentration of PGRs affected the percentage of in vitro callogenesis from the explants of Crinum americanum L. (Amaryllidaceae). Corresponding to these findings, the concentrations used in our study had an influential role in callus formation, as well.…”
Section: Discussionmentioning
confidence: 99%